2021
DOI: 10.1097/md.0000000000027373
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucocorticoids on mortality in severe COVID-19 patients

Abstract: Background: Since the start of the coronavirus disease 2019 (COVID-19) pandemic, there is an urgent need for effective therapies for patients with COVID-19. In this study, we aimed to assess the therapeutic efficacy of glucocorticoids in severe COVID-19. Methods: A systematic literature search was performed across PubMed, Web of Science, EMBASE, and the Cochrane Library (up to June 26, 2021). The literature investigated the outcomes of interest were mortality and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(185 reference statements)
0
9
0
1
Order By: Relevance
“…Patients 60 years of age or older receiving methylprednisolone had a lower mortality rate compared with patients receiving placebo . A recent meta-analysis study including observational studies and randomized trials involving different drugs suggested that treatment with corticosteroids reduces mortality and risk of progression to invasive mechanical ventilation in severe COVID-19 patients . Treatment with methylprednisolone has resulted in better clinical outcomes than treatment with dexamethasone, but larger randomized controlled studies are needed to confirm this finding. , …”
Section: Promising Covid-19 Therapiesmentioning
confidence: 99%
“…Patients 60 years of age or older receiving methylprednisolone had a lower mortality rate compared with patients receiving placebo . A recent meta-analysis study including observational studies and randomized trials involving different drugs suggested that treatment with corticosteroids reduces mortality and risk of progression to invasive mechanical ventilation in severe COVID-19 patients . Treatment with methylprednisolone has resulted in better clinical outcomes than treatment with dexamethasone, but larger randomized controlled studies are needed to confirm this finding. , …”
Section: Promising Covid-19 Therapiesmentioning
confidence: 99%
“…A total of 2 randomized clinical trials showed that using intravenous corticosteroids could reduce mortality (35,36). These findings are confirmed in a recent meta-analysis (37). However, it is important to point out the difference between administration, i.e., intravenous vs. inhalation, and setting, i.e., during hospital admission vs. home medication.…”
Section: Discussionmentioning
confidence: 80%
“…Some scholars suggest that corticosteroids in general are not expected to help as a class of drugs, but rather each steroid should be assessed individually because different drugs can be associated with a different number of genes [ 46 ]. Many published meta-analyses have evaluated the role of glucocorticoids in the COVID-19 epidemic, but they have not evaluated the comparison between glucocorticoids [ 45 , 47 51 ].…”
Section: Discussionmentioning
confidence: 99%